A 21st century campus aesthetic: photography, memory, performance - Flynn, Sarah Justine (Kansas State University, 2013)
Advancements in technology, architecture, landscape, planning and design, and education are being pursued in the 21st century. Unfortunately, the campuses of higher education institutions, which promote such advancements, do not reflect the vision of innovation and creativity. Rather, the exterior environments on college campuses portray a 19th century gardenesque landscape aesthetic, which emphasizes a “park-like” appearance and discounts ecological functions. The Kansas State University campus evidences a gardenesque aesthetic that arguably is not performing socially or ecologically to its fullest potential. This Master’s Project and Report uses an open space on K-State’s campus, Coffman Commons, to challenge its aesthetic performance. Campus landscape aesthetic performance can be improved by designing a community amenity that celebrates ecological processes, especially regarding stormwater, and involves the campus community in the design process. A conceptual framework, rooted in the Vitruvian Triad, directs the project’s methodology. Methods of photojournalism and design are conducted. Photojournalism is used to collect aesthetic responses of Coffman Commons from K-State students, faculty, and staff. Their photographic and textual responses inform the design process. The photography method allows each participant to confer importance to aspects of the landscape that moved them. Through photographic coding and content analysis, commonalities are discovered in the landscape with which each person identifies. The participants’ written descriptions further inform an understanding of expectations and hopes for Coffman Commons. Influenced by the photographic research and guided by set goals and objectives, the design method allows the innovation of a contextually specific and personable design solution for Coffman Commons. The design exhibits two community amenities which invite social activity to Coffman Commons. The amenities incorporate visible water systems (rain gardens and dry swales) - increasing the ecological performance of the Commons, and provide research opportunities for piezoelectric technology. The design also features inscriptions which honor Dr. Coffman and K-State Distinguished Faculty. This Master’s Project and Report transforms a gardensque campus landscape into a high-performance landscape that responsibly manages stormwater and enriches user experience.
Keywords: Coffman commons; Aesthetic performance; Photojournalism; Stormwater; Landscape Architecture (0390)